Pendampingan Pembuatan Bak Sampah Otomatis Berbasis Teknologi Internet of Things (IoT) Untuk Kantor Desa Aikmel Timur - Hidayat, Taupik; Lidiya; Aris Sudianto; Nurhidayati (Universitas Hamzanwadi, 2024)
Waste is a common issue in daily life that requires serious attention to be managed effectively. At the Aikmel Timur Village Office, waste management plays a crucial role in maintaining cleanliness and comfort in the work environment. To raise awareness among all village office staff about the importance of environmental cleanliness, a different approach is needed to encourage them to dispose of waste properly and orderly. Traditional trash bins often rely on manual systems to open, which can be inconvenient, especially when both hands are occupied or the system is unhygienic. As part of an internship program, I contributed to developing an innovation in the form of an Internet of Things (IoT)-based automatic trash bin. This innovation utilizes Arduino Uno and integrates key components such as the HC-SR04 sensor, servo motor, buzzer, and an adapter circuit. The HC-SR04 sensor detects the presence of waste intended for disposal, the servo motor serves as an automatic mechanism to open and close the bin, and the buzzer acts as an audio indicator to notify users that the system is active and ready for use. The development method began with identifying problems through a survey of workplace needs, followed by system design and implementation, as well as functional evaluation and benefit analysis. The result of this innovation is the creation of an automatic trash bin that not only facilitates waste disposal but also raises awareness about the importance of maintaining environmental cleanliness. Through this internship activity, it is hoped that this innovation can serve as a model to be widely implemented in villages, supporting better waste management practices. Keywords: Arduino Uno , buzzer, waste management, HC-SR04 sensor, servo motor.